The symphony of mission: playing your part in God's work in the world - Goheen, Michael W. (Baker Academic, 2019)
Story: listening to the symphony -- Simplicity: learning the notes -- Intentionality: the movements of mission -- Stewardship: displaying the glory of the Father through the work of our hands -- Service: displaying the love of Christ by washing the feet of the world -- The spoken word: displaying the power of the Holy Spirit by opening our mouths -- Listening: finding your place in God's symphony -- Performing: participating in God's symphony -- Pressing the sustain pedal: persevering in God's symphony.